Orientation‐Dependence of Thermal Depolarization and Phase Development in Bi1/2Na1/2TiO3‐BaTiO3 Single Crystals. Issue 12 (23rd September 2015) - Schneider, Deborah; Rödel, Jürgen; Rytz, Daniel; Granzow, Torsten
Abstract : The direction‐dependence of pyroelectric properties of (1 − x )Bi1/2 Na1/2 TiO3 − x BaTiO3 (BNT − 100 x BT) is investigated, using single crystal samples with well‐defined orientations for x = 0.036 and x = 0.063. The results are compared with those of temperature‐dependent measurements of the ferroelectric and dielectric hysteresis. The depolarization temperature T d of each crystal composition is found to depend on crystal orientation, a fact that is explained by differences in the stability of respective domain configurations. A rationalization is offered for the observation that T d differs from the ferroelectric‐relaxor transition temperature, depending on orientation. The hysteresis curves of BNT − 3.6BT are typical for a rhombohedral system with a ferroelectric‐relaxor transition, with polarization reversal close to T d occurring in a multistep process that includes decay of ferroelectric domains into polar nanoregions and re‐formation of domains. BNT − 6.3BT, a composition in the region of the morphotropic phase boundary, shows the same feature, but additionally is characterized by a field‐induced transition between rhombohedral and tetragonal symmetry. This combination results in an effective piezoelectric coefficient of d 33 * = 1886 pm/V.